Limbic oxytocin receptor expression alters molecular signaling and social avoidance behavior in female prairie voles (Microtus ochrogaster) - Nerio-Morales, Lina K.; Boender, Arjen J.; Young, Larry J.; Lamprea, Marisol R.; Smith, Adam S. (Frontiers in Neuroscience, 2024)
Introduction The social defeat paradigm is the most representative animal model to study social anxiety disorder (SAD) and its underlying neuronal mechanisms. We have previously reported that defeat progressively reduces oxytocin receptors (OXTR) in limbic regions of the brain over an eight-week period in female prairie voles (Microtus ochrogaster). Oxytocin receptors activate the mitogen-activated protein kinase (MAPK) pathway, which has been previously associated with the anxiolytic effects of oxytocin. Here, we assessed the functional significance of OXTR in stress-induced social avoidance and the response of the MAPK signaling pathway in the nucleus accumbens (NAc), anterior cingulate cortex (ACC), and basolateral amygdala (BLA) of female prairie voles. Methods In experiment 1, Sexually naïve adult female prairie voles were defeated for three consecutive days and tested a week after for social preference/avoidance (SPA) test. Control subjects were similarly handled without defeat conditioning. In experiment 2, sexually and stress naïve adult female prairie voles were bilaterally injected into the NAc, ACC, or the BLA with a CRISPR/Cas9 virus targeting the Oxtr coding sequence to induce OXTR knockdown. Two weeks post-surgery, subjects were tested for SPA behavior. Viral control groups were similarly handled but injected with a control virus. A subgroup of animals from each condition in both experiments were similarly treated and euthanized without being tested for SPA behavior. Brains were harvested for OXTR autoradiography, western blot analysis of MAPK proteins and quantification of local oxytocin content in the NAc, BLA, ACC, and PVN through ELISA. Results Social defeat reduced OXTR binding in the NAc and affected MAPK pathway activity and oxytocin availability. These results were region-specific and sensitive to exposure to the SPA test. Additionally, OXTR knockdown in the NAc, ACC, and BLA induced social avoidance and decreased basal MAPK activity in the NAc. Finally, we found that OXTR knockdown in these regions was associated with less availability of oxytocin in the PVN. Conclusion Dysregulation of the oxytocin system and MAPK signaling pathway in the NAc, ACC, and BLA are important in social behavior disruptions in female voles. This dysregulation could, therefore, play an important role in the etiology of SAD in women.